Dielectric and pyroelectric properties of the composites of ferroelectric ceramic and poly(vinyl chloride) - Olszowy, M. (Condensed Matter Physics, 2003)
The dielectric and pyroelectric properties of lead zirconate titanate/poly(vinyl chloride) [PZT/PVC] and barium titanate/poly(vinyl chloride) [BaTiO₃/ PVC] composites were studied. Flexible composites were fabricated in the thin films form (200−400 µm) by hot-pressed method. Powders of PZT or BaTiO₃ in the shape of 6 75 µm ceramics particles were dispersed in a PVC matrix, providing composites with 0−3 connectivity. Distribution of the ceramic particles in the polymer phase was examined by scanning electron microscopy. The analysis of the thermally stimulated currents (TSC) have also been done. The changes of dielectric and pyroelectric data on composites with different contents of ceramics up to 40% volume were investigated. The dielectric constants were measured in the frequency range from 600 Hz to 6 MHz at room temperature. The pyroelectric coefficient for BaTiO₃/PVC composite at 343 K is about 35 µC/m²K which is higher than that of β-PVDF (10 µC/m²K).